Barriers to responding to reproductive coercion and abuse among women presenting to Australian primary care - Molly Wellington; Kelsey Hegarty; Laura Tarzia (BMC, 2021)
Abstract Background Reproductive coercion and abuse is defined as any behaviour that seeks to control a woman's reproductive autonomy. In Australia, women often access reproductive health care through a primary care clinician, however, little is known about clinicians' experiences responding to reproductive coercion and abuse. This study aims to address this gap by exploring the barriers to responding to reproductive coercion and abuse in Australian primary care. Methods In this qualitative study, twenty-four primary care clinicians from diverse clinical settings in primary care across Australia were recruited to participate in a semi-structured interview. Data were analysed thematically. Results Through analysis, three themes were developed: It's not even in the frame; which centred around clinicians lack of awareness around the issue. There's not much we can do, where clinicians described a lack of confidence in responding correctly as well as a lack of services to refer on to. Lastly There's no one to help us, explaining the disconnect between referral services and primary care as well as the impacts of lack of abortion on women experiencing reproductive coercion and abuse. Conclusions Clinicians expressed similar experiences of barriers to respond to reproductive coercion and abuse. Many clinicians felt ill-equipped to identify and respond to reproductive coercion and abuse. Some clinicians hadn't received any formal training, others were trained but had nowhere to refer women. Further complicating responses was a lack of support from referral services. This study highlights the need for more training and a streamlined referral pathways for women who experience reproductive coercion and abuse, as well as better access to reproductive health services in rural areas.